Women’s Bodies as Battlefields: Breast Amputation and Genital Mutilation in the Overlooked Genocidal Conflict in Ethiopia - Berhanu, Girma (Advances in Social Sciences Research Journal, 2025)
The situation in Ethiopia’s Amhara region has deteriorated into a critical humanitarian and human-rights emergency. Emerging evidence from besieged localities indicates an escalation of atrocities that transcend previously documented patterns of violence. Verified testimonies and secondary reports detail widespread killings accompanied by systematic sexual and gender-based violence, including acts intended to cause profound physical and psychological harm. These violations appear to be strategically employed as instruments of terror and social destabilization. The proliferation of graphic content across digital platforms has generated significant secondary trauma among affected populations, while simultaneously underscoring the role of media in shaping collective perception and response. Notwithstanding the severity of these crimes, international awareness and condemnation remain disproportionately limited, revealing a persistent gap between global normative commitments and practical engagement. Concurrently, ongoing drone strikes against civilian populations exacerbate the humanitarian toll, contributing to cumulative suffering and displacement. Drawing on verified interviews with relatives of victims and triangulated findings from human-rights and academic sources, this study situates the documented abuses within the broader context of conflict-related sexual violence and violations of international humanitarian law. Building on prior research concerning gendered violence against men in the region, the findings contribute to a growing body of empirical evidence suggesting the commission of acts that may amount to crimes under international law.